Hollow doughnut shaped mesoporous silica nanoparticles for reduction of the thermal expansion coefficient of poly(ether sulfone) films. (5th March 2018) - Vo, Nhat Tri; Patra, Astam K.; Kim, Dukjoon
Abstract : A hollow doughnut shaped mesoporous silica nanoparticle filler that significantly enhances the dimensional thermal stability without sacrificing the optical properties of poly(ether sulfone) films is reported. Abstract : A decrease in the coefficient of thermal expansion of poly(ether sulfone) films is achieved through the incorporation of hollow doughnut shaped mesoporous silica nanoparticles (hd-MSNs). A new class of silica nanoparticles with an unprecedented structural morphology is synthesized by hydrolysis of tetraethyl orthosilicate (TEOS) in the presence of cetyltrimethylammonium bromide (CTAB), l -arginine, and ammonium metatungstate (AMT) composite templates, all in aqueous ethanol. 46.1% and 48.0% decreases in the coefficient of thermal expansion (CTE) of poly(ether sulfone) films are observed in the range of 30–90 °C and 30–150 °C, respectively, when 2.0 wt% of hd-MSNs are loaded. Furthermore, the small size (<50 nm diameter) of doughnut shaped mesoporous silica nanoparticles helps to decrease light scattering, and thus maintains the high transmittance of the nanocomposite films. The effect of the hd-MSN was also investigated on both the thermal and mechanical stability. We expect that the hd-MSN synthesized in this study can be used as a promising filler to improve the thermal and mechanical stability of the PES substrate without losing its optical transparency.